IDEAS OF LABOR EDUCATION OF PRE-SCHOOL AND PRIMARY SCHOOL CHILDREN (END OF XIXth - EARLY XXth CENTURY) - Antipіn Evgen B. (Educological discourse, 2014)
The article consist the common characteristic of the problem of preschool and primary school children labor education on the period of the end of XIX-th – the beginning of XX-th century. It shows the main ideas of solution of the presented problem.